Determinants of supply chain performance: Moderating role of firm size in tourism hotel industry in Indonesia - Djoko Roespinoedji; Afghan Prawira EP; Ismail Solihin; Mohd Haizam Mohd Saudi; Omar Alaeddin (International Journal of Supply Chain Management, 2019)
In recent decade, Supply Chain Management is emphasized for determining the performance of firms in any industry. SCM contribute in enhancing performance of firms to perform better in competitive environment. Current study emphasized on predictors of supply chain performance in tourism industry of Indonesia. Study entails integration with supplier and information sharing to be influential on supply chain performance. The study determined the relationship between exogenous and endogenous variable with the moderating role of firm size. Smart PLS is used to analyze the data collected from respondents associated with tourism industry of Indonesia. Measurement model and structure equation model is used by using PLS to analyze direct effect and to determine moderating role. The study can be considered as empirical work that investigates important factors to be influential on supply chain performance of tourism hotel industry of Indonesia.